Organic Growth Disciplines : a Strategic Framework for Imagining Business Growth Opportunities - Sudharshan, Devanathan (Emerald Publishing Limited, 2019)
If your firm doesn't grow sustainably, can you grow professionally? In Organic Growth Disciplines, business expert Devanathan Sudharshan introduces a new framework for exploring the fuzzy front end of the search for growth opportunities.